Narcolepsy with and without cataplexy, idiopathic hypersomnia with and without long sleep time: a cluster analysis - Šonka, Karel; Šusta, Marek; Billiard, Michel (Sleep medicine, 2015)
BACKGROUND: The successive editions of the International Classification of Sleep Disorders (ICSD) reflect the evolution of the concepts of various sleep disorders. This is particularly the case for central disorders of hypersomnolence, with continuous changes in terminology and divisions of narcolepsy, idiopathic hypersomnia, and recurrent hypersomnia. According to the ICSD 2nd Edition (ICSD-2), narcolepsy with cataplexy (NwithC), narcolepsy without cataplexy (Nw/oC), idiopathic hypersomnia with long sleep time (IHwithLST), and idiopathic hypersomnia without long sleep time (IHw/oLST) are four, well-defined hypersomnias of central origin. However, in the absence of biological markers, doubts have been raised as to the relevance of a division of idiopathic hypersomnia into two forms, and it is not yet clear whether Nw/oC and IHw/oLST are two distinct entities. With this in mind, it was decided to empirically review the ICSD-2 classification by using a hierarchical cluster analysis to see whether this division has some relevance, even though the terms "with long sleep time" and "without long sleep time" are inappropriate. RESULTS: The cluster analysis differentiated three main clusters: Cluster 1, "combined monosymptomatic hypersomnia/narcolepsy type 2" (people initially diagnosed with IHw/oLST and Nw/oC); Cluster 2 "polysymptomatic hypersomnia" (people initially diagnosed with IHwithLST); and Cluster 3, narcolepsy type 1 (people initially diagnosed with NwithC). CONCLUSIONS: Cluster analysis confirmed that narcolepsy type 1 and polysymptomatic hypersomnia are independent sleep disorders. People who were initially diagnosed with Nw/oC and IHw/oLST formed a single cluster, referred to as "combined monosymptomatic hypersomnia/narcolepsy type 2."
Keywords: Humans; Narcolepsy type 1; lidé středního věku; polysomnografie; Female; Narcolepsy; mladý dospělý; dospělí; poruchy nadměrné spavosti; Cluster Analysis; Polysomnography; lidé; narkolepsie; Narcolepsy type 2; Idiopathic hypersomnia; Adult; ženské pohlaví; Male; Middle Aged; shluková analýza; Disorders of Excessive Somnolence; Young Adult; Factor analysis; Cluster analysis; mužské pohlaví